Local administrations as agents of enforcement of Transparency Law by non-profit organizations. Analysis of the Barcelona City Council case - Molina Rodríguez-Navas, Pedro; Simelio Solà, Nuria; Rodríguez Breijo, Vanessa (Revista General de Información y Documentación, 2018)
The application of the new obligations established by the Transparency Law to certain non-profit organisations presents operational challenges for effective monitoring and control. However, for these organizations to gain the confidence of its stakeholders and to fight inefficient management, transparency is essential. This article presents a case study of the organisations that have received grants or public subsidies to the Barcelona City Council in 2016 are obliged to comply with the Law of Transparency of Catalonia. The principal aim is to determine if the organisations to which it grants subsidies are included among those that are subject to this legal requirement and if they really meet those requirements in order to allow the accountability of citizens. To evaluate transparency the TransparEnt project is used.  This is an own and proven methodology based on a series of indicators that evaluate the quality and transparency of the information. Therefore, there is no legal analysis of the Transparency Law, nor an assessment from this perspective, but we start to establish indicators based on the Transparency Law, to evaluate the information displayed on the websites of the organisations. The principal results show the difficulties of the Barcelona City Council to correctly monitor the transparency of the organizations. The conclusions propose the creation of shared resource structures and the reinforcement of training and awareness strategies to overcome the lack of tradition, knowledge and resources that both non-profit organisations and local public administrations suffer from.
Keywords: Transparency; non-profit organisations; NGOs; local administrations; public administrations; subsidies; digital communication; Internet; participation; accountability